1077. Understanding the Psychosocial Burden Associated with Hospitalization Among Adults Diagnosed with COVID-19 in the United States. (15th December 2022) - Ansari, Wajeeha; Draica, Florin; Atkinson, Joanna; Annunziata, Kathy; Maculaitis, Martine C; Scott, Amie
Abstract: Background: Due to the coronavirus disease 2019 (COVID-19) pandemic in the United States (US), public health officials sought to reduce transmission. However, the psychosocial impact associated with COVID-19 has received less attention. This study describes psychosocial burden among adults diagnosed with COVID-19 and assesses the unique impact on those who had a COVID-19 hospitalization. Methods: This cross-sectional retrospective study used 2021 US National Health and Wellness Survey (NHWS; N=75, 098) data. NHWS is an annual web-based self-report survey of the US general adult population (aged ≥ 18 years). Results were weighted to reflect the population on age, gender, race/ethnicity, and education based on US Census. Among adults who self-reported a COVID-19 diagnosis, those with COVID-related hospitalization, emergency room (ER) visit/no hospitalization, and no hospitalization/no ER visit were descriptively compared on demographics, health characteristics, and psychosocial burden measures. Results: Almost 16 million adults had a COVID-19 diagnosis in the past year; of these, 8% had a COVID-related hospitalization, and 6% had a COVID-related ER visit/no hospitalization. Compared to adults with no ER visit/no hospitalization or ER visit/no hospitalization, those with a hospitalization were more often male, college educated, and employed. Relative to those with no ER visit/no hospitalization, adults with a hospitalization were more often diagnosed, either pre- or post-COVID-19 diagnosis, with allergies (47% vs 38%), asthma (20% vs 11%), pain (37% vs. 25%), headache (25% vs 16%), migraine (27% vs 15%), type 2 diabetes (16% vs 10%), dry eye (25% vs 12%), and sleep apnea (15% vs 11%). Adults with a hospitalization had lower mental, physical, and general health-related quality of life, 2-3.4 times higher work/non-work impairment, and 2 times higher positive depression screen rate than those with no ER visit/no hospitalization. Conclusion: US adults with a COVID-related hospitalization had higher psychosocial burden than those without a hospitalization on several domains. Accordingly, reducing COVID-related hospitalizations, particularly among the employed and those with comorbidities, will be vital to help mitigate this burden. Disclosures: Wajeeha Ansari, MPH, Pfizer Inc.: Stocks/Bonds Florin Draica, MD, Pfizer Inc.: Stocks/Bonds Joanna Atkinson, MD, Pfizer Inc.: Stocks/Bonds Kathy Annunziata, MA, Pfizer: Advisor/Consultant|Pfizer: Employee of Cerner Enviza, which received funding from Pfizer to conduct and report on the study Martine C. Maculaitis, PhD, Cerner Enviza: Employee of Cerner Enviza, which received funding from Pfizer to conduct and report on the study. Amie Scott, MPH, Pfizer Inc.: Stocks/Bonds.